The Effect of Flexiquiz Technology Integrated Problem Based Learning Model on Creative Thinking Skills and Learning Outcomes of Class X Students in History Subject - Rarasanti, Pramodia Dyah; Umamah, Nurul; Marjono, Marjono; Sumardi, Sumardi (History Education, University of Jember, 2024)
Technological developments in the learning process are able to provide freedom to design and design innovative, creative and adaptive media according to the needs of students. These 4C skills include critical thinking, creativity and being able to think collaboratively. This can be collaborated with the use of a Problem Based Learning model that emphasizes Creative Thinking in students. This research uses a quantitative approach with experimental research type. The research design used a quasi-experimental model with a pretest-posttest, non-equivalent control group design. The sample consisted of 70 students in classes X-A and X-D SMAN 2 Tanggul. Data analysis technique using ANCOVA test. The results of this study obtained: 1) the results of ANCOVA test showed sig value. 0.005 <0.05 Creative Thinking Skills, which means it shows a significant effect of applying the PBL model integrated with FlexiQuiz technology on creative thinking and the value of the partial eta squared of 0.474, which means there is a great influence of applying the PBL model integrated with FlexiQuiz technology on students' Creative Thinking Skills; 2) the results of the ANCOVA test on learning outcomes data show sig. 0.003<0.05 partial eta squared of 0.113 is classified as a medium effect of applying the PBL model on student learning outcomes